Demographic analysis: an update of randomized controlled studies in prostatic oncology - Wehbi, Elias; Hersey, Karen; Finelli, Tony; Fleshner, Neil E. (Canadian Urological Association Journal, 2013)
Introduction: Results from randomized trials are least prone to systematic bias and represent the highest level of evidence in medical practice. We carried out a demographic analysis examining randomized controlled trials (RCTs) in prostate cancer. Particular emphasis was placed on newly conducted phase II/III RCTs between January 1997 and March 2006. Methods: We searched the MEDLINE database using the heading “prostate neoplasms” between January 1997 and March 2006. The results were then crossed with the MeSHs “Clinical trial.mp. OR clinical trial.pt. OR random:.mp. OR tu.xs;” this cross-checking is considered an optimal search strategy for detecting RCTs in MEDLINE® literature. The search yielded 7831 articles in total for the defined period. Of this total number, 7314 articles were manually analyzed and excluded as they did not represent RCTs. The qualifying 517 articles were then analyzed with emphasis on modality of therapy, cohort size, principal author, participating country and journal type. Results: Among the 517 randomized trials, most trials investigated medical therapies (42.7%). This was followed by diagnostic studies (13.2%), while the remaining categories made up 44.1%. A trend towards more completed RCTs is noted in the later years of the cohort. Cohort sizes were generally greater than 100 participants (63.1%). Urologists were the lead investigators in 48.2% of the trials. Trials were largely conducted in Europe and the United States (43.1% and 38.3%, respectively). About 7% of studies were based in Canada. Articles were generally published in surgical journals (48.4%), followed by medical journals (36.9%). Conclusions: Given that initial searches yielded nearly 8000 articles listed as RCTs in prostatic oncology, only a small percentage (5.4% to 8.6%) of these were actually RCTs which reported novel results. Most of the published data were either review articles or commentaries. It is abundantly clear that new recruitment strategies need to be developed to encourage patients to enrol in RCTs and that such studies need to be undertaken in urologic oncology to provide definitive answers to the abundant and unanswered questions in urologic oncology. Introduction : Les résultats d’essais randomisés sont les moins sujets à une partialité d’emblée et représentent le plus haut niveau de données probantes en médecine. Nous avons mené une analyse démographique des essais contrôlés et randomisés (ECR) sur le cancer de la prostate, en portant attention plus particulièrement aux plus récents essais de phase II/III, menés entre janvier 1997 et mars 2006. Méthodologie : Nous avons interrogé la base de données MEDLINE avec le titre « prostate neoplasms » pour la période entre janvier 1997 et mars 2006. Les résultats ont ensuite été recoupés avec une recherche dans la base de données MeSH avec les clés « Clinical trial.mp. OU clinical trial.pt. OU random:.mp. OU tu.xs »; ce recoupement est vu comme une stratégie optimale de recherche pour cerner les ECR dans les articles classés dans MEDLINE. La recherche a produit un total de 7 831 articles pour la période définie. De ce nombre, 7 314 articles ont été analysés manuellement et exclus puisqu’ils ne traitaient pas d’ECR. Les 517 articles admissibles ont ensuite été analysés, avec une attention particulière aux modalités de traitement, à la taille de la cohorte, à l’auteur principal, au pays participant et au type de périodique. Résultats : Sur les 517 essais randomisés, la plupart examinaient des traitements médicamenteux (42,7 %). Venaient ensuite les études diagnostiques (13,2 %), alors que le reste (44,1 %) entrait dans les autres catégories. On a noté une tendance vers une complétude plus élevée des ECR dans les dernières années de la période. Les cohortes comptaient habituellement plus de 100 participants (63,1 %). Les chercheurs principaux étaient des urologues dans 48,2 % des essais. La grande majorité des essais ont été menés en Europe et aux États-Unis (43,1 % et 38,3 %, respectivement). Environ 7 % des études étaient menées au Canada. Règle générale, les articles étaient publiés dans des revues en chirurgie (48,4 %), suivies des revues médicales (36,9 %). Conclusions : Comme les recherches initiales ont généré près de 8 000 articles classés comme des ECR en oncologie prostatique, seul un petit pourcentage (5,4 % à 8,6 %) de ces articles était en fait des ECR signalant des résultats inédits. La majorité des données étaient publiées sous forme d’articles de synthèse ou de commentaires. Il est très clair que de nouvelles stratégies de recrutement doivent être établies pour encourager les patients à s’inscrire aux ECR et que de tels essais doivent être entrepris en oncologie urologique afin de fournir des réponses claires aux nombreuses questions qui restent à élucider dans le domaine.